Does Arsenic-Contaminated Drinking Water Limit Early Childhood Development in Bangladesh? - Haque, Sabrina S. (World Bank, Washington, DC, 2017)
Arsenic contamination in shallow groundwater aquifers remains a major barrier to providing access to safe drinking water in Bangladesh. Chronic exposure to arsenic has been shown to cause serious health impacts, including various cancers, skin lesions, neurological damage, heart disease, and hypertension. Numerous epidemiological studies have shown cognitive impacts on memory, linguistic-abstraction, attention, learning, and physical ability. The neurotoxic effects of arsenic could be particularly harmful for children during their critical growth periods and have impacts on early childhood development. This study uses cross-sectional data from the nationally representative 2012-13 Bangladesh Multiple Indicator Cluster Survey to investigate the effects of arsenic contamination in drinking water on early childhood development outcomes in a sample of around 7,500 children ages 3-5 years. Early childhood development is measured in four skills domains: literacy-numeracy, physical, social-emotional, and learning using the Early Childhood Development Index. Arsenic contamination is measured in source drinking water at the cluster-level. After controlling for a range of demographic, social, and economic characteristics of households, the results show that arsenic contamination is significantly and negatively associated with the overall Early Childhood Development Index, on outcomes within the physical, social-emotional, and learning skills domains. Further, there is a clear dose-response relationship, where those children with exposure to higher concentrations of arsenic have worse developmental outcomes.